RETRACTED: A Strain of an Emerging Indian Xanthomonas oryzae pv. oryzae Pathotype Defeats the Rice Bacterial Blight Resistance Gene xa13 Without Inducing a Clade III SWEET Gene and Is Nearly Identical to a Recent Thai Isolate - Carpenter, Sara C. D.; Mishra, Prashant; Ghoshal, Chandrika; Dash, Prasanta K.; Wang, Li; Midha, Samriti; Laha, Gouri S.; Lore, Jagjeet S.; Kositratana, Wichai; Singh, Nagendra K.; Singh, Kuldeep; Patil, Prabhu B.; et al. (Frontiers in Microbiology, 2018)
The rice bacterial blight pathogen Xanthomonas oryzae pv. oryzae (Xoo) injects transcription activator-like effectors (TALEs) that bind and activate host ‘susceptibility’ (S) genes important for disease. Clade III SWEET genes are major S genes for bacterial blight. The resistance genes xa5, which reduces TALE activity generally, and xa13, a SWEET11 allele not recognized by the cognate TALE, have been effectively deployed. However, strains that defeat both resistance genes individually were recently reported in India and Thailand. To gain insight into the mechanism(s), we completely sequenced the genome of one such strain from each country and examined the encoded TALEs. Strikingly, the two strains are clones, sharing nearly identical TALE repertoires, including a TALE known to activate SWEET11 strongly enough to be effective even when diminished by xa5. We next investigated SWEET gene induction by the Indian strain. The Indian strain induced no clade III SWEET in plants harbouring xa13, indicating a pathogen adaptation that relieves dependence on these genes for susceptibility. The findings open a door to mechanistic understanding of the role SWEET genes play in susceptibility and illustrate the importance of complete genome sequence-based monitoring of Xoo populations in developing varieties with effective disease resistance.